Sustainable Development of Water Resources Carrying Capacity Based on System Dynamics: A Case Study of Ganzhou City - WANG Xiaojun; YANG Huan; LI Zhenping; YAN Wenfeng; LAN Sijiao; DU Chao (Renmin Zhujiang)
As Ganzhou is the birthplace of Ganjiang River,Dongjiang River,and Beijiang River (“Three Rivers”),the security and sustainable development of its water resources are of great significance to the ecological security and sustainable development of both the Yangtze River Economic Belt downstream and the Guangdong-Hongkong-Macao Greater Bay Area.Thus,seeking the optimal sustainable development mode that Ganzhou's water resources can carry and ensuring the safety and sustainable use of those water resources are currently urgent issues to be solved.In this study,we employ the system dynamics method to build a system dynamics model of Ganzhou's water resources carrying capacity by analyzing its influencing factors and the system feedback loop and dividing the carrying capacity system into three sub-systems of social economy,water resources,and water environment.Moreover,four scenarios of normal development,economic priority,environmental priority,and comprehensive and coordinated development are designed to simulate Ganzhou's water resources carrying capacity during 2020—2035 and dynamically evaluate and simulatively predict its sustainable development capacity under each scenario.The results indicate that among the four scenarios,all the normal development and economic priority scenarios that sorely pursue the continuation of the current development status of social economy and the environmental priority scenario that protects water resources at the expense of social economy development fail to guarantee the sustainable development of water resources and social economy.In contrast,under the comprehensive and coordinated development mode,the chemical oxygen demand (COD) emissions will remain at a low level of 132 900 t by 2035 while economic development rises to a relatively high level,with GDP reaching 1 197.13 billion CNY.It follows that this mode not only ensures economic development but also takes into account the ecological environment.Therefore,the comprehensive and coordinated development scenario that comprehensively considers social economy development,environmental protection,and other factors is the optimal sustainable development mode that can be carried by water resources.